2023
DOI: 10.1002/cre2.709
|View full text |Cite
|
Sign up to set email alerts
|

Dental implant surface morphology, chemical composition, and topography following double wavelength (2780/940 nm) laser irradiation. An in vitro study

Abstract: Objective: The aim of this in vitro study was to evaluate morphology alterations, chemical composition, and topography of moderately rough dental implants following double-wavelength laser irradiation.Material and Methods: Commercial-grade titanium dental implants representing different surface characteristics (Osseospeed [OS], TiUnite [TiU], and Roxolid SLActive [RS]) were used. Laser irradiation was performed using a computer-controlled robotic device with calibrated energy/power settings and deionized water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(82 reference statements)
0
1
0
Order By: Relevance
“…In the research of Scarano et al, the irradiation of the SLA disk surface with Er:YAG laser depicted similar results, leading to an increase in TiO 2 layer [33]. Additionally, the experiment of Ercan et al showed treatment with the Er,Cr:YSGG laser at settings above 2 W resulted in an increase in oxygen levels and a decrease in titanium levels due to oxidation [34,35]. The effects of the chemical composition of the disks on cell and tissue behaviors warrant comprehensive in vitro and in vivo studies.…”
Section: Discussionmentioning
confidence: 82%
“…In the research of Scarano et al, the irradiation of the SLA disk surface with Er:YAG laser depicted similar results, leading to an increase in TiO 2 layer [33]. Additionally, the experiment of Ercan et al showed treatment with the Er,Cr:YSGG laser at settings above 2 W resulted in an increase in oxygen levels and a decrease in titanium levels due to oxidation [34,35]. The effects of the chemical composition of the disks on cell and tissue behaviors warrant comprehensive in vitro and in vivo studies.…”
Section: Discussionmentioning
confidence: 82%
“…As an advantage, Ti has mechanical properties that support the functional load of mastication and, at the same time, it is biocompatible with bone tissue [6][7][8][9] . In the last years, several studies related to morphology, roughness, chemical composition, and wettability have sought to expand the range of possible applications of dental implants have been carried [10][11][12][13][14] . Despite numerous efforts to establish a correlation between the microstructure of the Ti implant, and biological responses at the cellular and molecular level, this point has not yet been fully clarified.…”
Section: Introductionmentioning
confidence: 99%